PERSEPSI MAHASISWA TENTANG KUALITAS PELAYANAN KANTIN FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - FERDIAN, FERI; Kasmita, Kasmita; Waryono, Waryono (Journal of Home Economics and Tourism, 2014)
The purpose of research is to determine the college student’s perceptions about the quality of service cafeteria FT UNP. This research consists of five indicators are: reliability, responsiveness, assurance, empathy, and  tangibles. This type of research is descriptive research using survey method. Population in this research amounted to 7233 people. Sampling technique is non probability sampling, using insidental sampling. Sample number in this research amounted to 100 people. Data collection using a questionnaire based on a Likert scale that tested for validity and reliability.  Based on the results of the study concluded that in general the college students’perceptions about quality of service cafeteria FT UNP by 8% of respondents expressed very well, 62% of respondents said good, 21% of respondents said sufficiently, and 9% of respondents said less.